Kajian Pengaruh Dosis Atonik dalam Perlakuan Pembelahan Umbi Bibit terhadap Pertumbuhan dan Hasil Bawang Merah (Allium cepa L.) - Wora, Ardi; Raharjo, Krisantus Tri Pambudi; Neonbeni, Eduardus Yosef (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2024)
Studies were carried out in KM 9 Sasi Village, Kota District, North Central Timor Regency (TTU) to test the effect of atonic doses in the distribution of seed tubers on the growth and yield of shallots (Allium Cepa L.). A fully randomized design (CRD) was used. ) Faculty 7 repetitions. The first factor is tuber cleavage (B), namely: without cleavage (B0), halved (B1), the second factor is the concentration of the atonic ZPT doses (D), which consists of 4 steps, namely: control without atonic D0), 0.5 ml / L liter of water (D1), dose of 1 ml / L liter of water (D2), dose of 1.5 ml / L liter of water (D3). The results of the study showed that treatment of tuber division tended to decrease the number of tubers per lump, but increased tuber weight per lump and weight per tuber. Treatment of semen cleavage by immersion in an atonic solution of 1.5 ml / l increases the yields per lump by 14.78% higher than treatments without tuber division.